Evaluation of two dipping methods for sampling immature Culex and Ochlerotatus mosquitoes (Diptera: Culicidae) from artificial containers - Paul T. Leisnham; David P. Slaney; Philip J. Lester; Philip Weinstein (New Zealand Journal of Marine and Freshwater Research, 2005)
Monitoring changes in populations of immature (larvae and pupae) mosquitoes are fundamental to determining mosquito‐borne disease risk. Dipping is the most common method used to sample immature mosquitoes, but it can be biased towards particular species and instars. We aimed to assess the generality of the findings of Mori (1989), who showed that stirring the water of artificial containers gave more consistent and accurate samples of Ochlerotatus togoi compared with conventional dipping without prior stirring. Five water‐filled artificial containers were placed in each of pastureland, urbanland, and native forest. These containers were subsequently colonised by Culex pervigilans and O. notoscriptus and were used to compare two dipping methods using a plastic dipper. One method involved removing the container from the field and stirring the water before sampling (destructive sampling), and was compared with a conventional field dipping method without prior stirring (field dipping). Results from this study showed that when comparing samples from the two methods, destructive sampling gave estimates that had very strong and better correlations with absolute counts, and were more accurate and consistent. Field dipping generally underestimated O. notoscriptus, possibly because it did not sample the bottom of the container where Ochlerotatus larvae browse detrital sediments. When using estimates from destructive sampling compared with field dipping, the relationship between mosquito density and land use was more similar to the relationship between absolute counts and land use across all population measures used. The results suggest that destructive sampling may be a more reliable mosquito sampling method than conventional field dipping when studying questions on mosquito ecology.